2021
DOI: 10.3991/ijim.v15i10.20707
|View full text |Cite
|
Sign up to set email alerts
|

Real Time System Monitoring and Analysis-Based Internet of Things (IoT) Technology in Measuring Outdoor Air Quality

Abstract: The presence of large peatland in Riau, Indonesia, could cause air pollution due to peatland fires which causes the presence of thick smoke every year in Riau,  dis-rupting human activities. In order to monitor the air quality, in this paper,  the main advantage of the  Internet of Things (IoT) is the ability to transfer data over the network without requiring human-to-human or human interaction to the com-puter   used. In this paper, we propose an air quality monitor that can display web-based information to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…The research method for developing this system is sequenced in stages that was adapted from [17], which comprised of design development, hardware construction, system development followed by integration and validation. Figure 1 illustrates the overall design concept of the proposed voice-enabled lamp control system, integrated with IOT.…”
Section: Methodsmentioning
confidence: 99%
“…The research method for developing this system is sequenced in stages that was adapted from [17], which comprised of design development, hardware construction, system development followed by integration and validation. Figure 1 illustrates the overall design concept of the proposed voice-enabled lamp control system, integrated with IOT.…”
Section: Methodsmentioning
confidence: 99%
“…This stage is carried out when the tool has been repaired after repair and has been connected to IoT [19] [20]. From the results of the final test, the tool made, namely IoTbased pulse oximetry, can already be used for the community and for monitoring it can also be done by the Sapta Taruna Health Center.…”
Section: Product Developmentmentioning
confidence: 99%
“…As a result, it was found that the largest emitter of pollutants is the industry, followed by urban traffic and domestic heating. [10] used MQ-135 and DHT11 sensors for the detection of CO, CO 2 , alcohol, air temperature, and humidity, and transmission through an IoT network composed of an Arduino UNO and a Raspberry Pi. As a result, a platform for monitoring and issuing early warnings of the monitored air quality was configured.…”
Section: State Of the Art In The International Contextmentioning
confidence: 99%